COVID-19 and Tuberculosis: Two Knives in a Sheath - Sundaram, Kishore K. M.; Kumar, Attuluri V.; Alphonsa, Thomas; Rajendran, Sangeetha; Rajamanickam, Krishnamurthy; Alemtoshi; Balachandar, Vellingiri; Bharali, Pranjal; Giridharan, Bupesh; Saravanan, Konda Mani (Coronaviruses, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2) has caused a global human outbreak, making it a more serious threat to human health than any other infectious disease. Coronavirus infectious disease 2019 (COVID-19) has severely affected the lifestyles of people around the world and caused high mortality throughout the world. In both pandemic and seasonal influenza, co-infection of COVID-19 with other diseases has been linked to worse outcomes. The literature revealed that it is characteristically associated with comorbidities such as hypertension, blood pressure, obesity, cardiovascular diseases, and other microbial infections. Furthermore, microbial coinfections worsen respiratory viral infections and are a common cause of death in influenza pandemics. Deplorably, Tuberculosis (TB) is also a dreadful lung infection and attains cytokine equilibrium with host cells to maintain the latent stage. Studies showed that human coronaviruses (hCoV) activate latent TB to an active state due to unregulated cytokine production, called a cytokine storm. The present review concisely discusses the reason and status of co-infection of COVID-19 with TB based on previous case reports, cohorts, and scientific studies. COVID-19 patients are prone to be infected with TB and vice-versa in TB-prone areas. The therapeutic opportunities for overcoming the COVID-19 induced cytokine storm have also been emphasized by the present clinical trial candidates. In conclusion, we recommend categorizing the patients based on their medical history and cured or latent TB patients should be particularly closely monitored. They should be tested for Interferon Gamma Release Assay (IGRA) regularly on and after COVID-19 infection.
Keywords: vaccines